2016
DOI: 10.1039/c5cp05764g
|View full text |Cite
|
Sign up to set email alerts
|

The origin of luminescence from di[4-(4-diphenylaminophenyl)phenyl]sulfone (DAPSF), a blue light emitter: an X-ray excited optical luminescence (XEOL) and X-ray absorption near edge structure (XANES) study

Abstract: The electronic structure and optical properties of di[4-(4-diphenylaminophenyl)phenyl]sulfone (denoted as DAPSF), a highly efficient fluorophor, have been investigated using X-ray excited optical luminescence (XEOL) and X-ray absorption near edge structure (XANES) spectroscopy at excitation energies across the C, N, O K-edges and the sulfur K-edge. The results indicate that the blue luminescence is mainly related to the sulfur functional group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
2
2
1
1
Order By: Relevance
“…Angle-resolved TEY and FY NEXAFS spectra of the polymeric membranes at the sulfur K-edge are shown in Figure : two peaks appeared in all spectra, the most intense peak (peak 2), with an energy of 2480.1 eV, and the first peak (peak 1) at 2477.3 eV, followed by broad features in the continuum. These spectra are similar to previously reported S1s NEXAFS spectra of sulfone derivatives: poly­(ether sulfone) resin, di­[4-(4-diphenylaminophenyl)­phenyl] sulfone film, and 1,10-sulfonyldibenzene powder . Following the assignment of Behyan et al peak 2 is mostly attributed to the sulfur 1s → σ*­(S–O)/σ*­(S–C) transition and peak 1 is attributed to the sulfur 1s → σ*­(S–O)/σ*­(S–C) transition that mixes with the π*­(C=C) density of the phenyl ring.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Angle-resolved TEY and FY NEXAFS spectra of the polymeric membranes at the sulfur K-edge are shown in Figure : two peaks appeared in all spectra, the most intense peak (peak 2), with an energy of 2480.1 eV, and the first peak (peak 1) at 2477.3 eV, followed by broad features in the continuum. These spectra are similar to previously reported S1s NEXAFS spectra of sulfone derivatives: poly­(ether sulfone) resin, di­[4-(4-diphenylaminophenyl)­phenyl] sulfone film, and 1,10-sulfonyldibenzene powder . Following the assignment of Behyan et al peak 2 is mostly attributed to the sulfur 1s → σ*­(S–O)/σ*­(S–C) transition and peak 1 is attributed to the sulfur 1s → σ*­(S–O)/σ*­(S–C) transition that mixes with the π*­(C=C) density of the phenyl ring.…”
Section: Resultssupporting
confidence: 89%
“…Following the assignment of Behyan et al peak 2 is mostly attributed to the sulfur 1s → σ*­(S–O)/σ*­(S–C) transition and peak 1 is attributed to the sulfur 1s → σ*­(S–O)/σ*­(S–C) transition that mixes with the π*­(C=C) density of the phenyl ring. The shoulder on the lower energy edge of peak 2, mentioned by Behyan et al, was neither observed here in the TEY NEXAFS spectra nor at Calderon and Zhang et al works. Since NEXAFS is a local chemical probe, groups that are electronically isolated from the sulfone groups may not interfere, and based on this, we believe that this is the proper assignment, dominated by contribution of the sulfone bond.…”
Section: Resultscontrasting
confidence: 67%
See 2 more Smart Citations
“…XEOL-сигнал в комбинации с другими типами рентгеновской спектроскопии, например, околопороговой тонкой структуры XANES (X-ray Absorption Near Edge Structure) или протяженной тонкой структуры спектров рентгеновского поглощения EXAFS (Extended X-ray Absorption Fine Structure) в последние годы эффективно используется для исследования природы и Оптика и спектроскопия, 2022, том 130, вып. 3 механизмов оптической люминесценции в различных материалах [18][19][20][21][22][23], а также в качестве способа мониторинга радиоактивного повреждения образцов в рентгеноструктурном анализе белков [24] и высвобождения лекарственных препаратов из наноконтейнеров при варьировании кислотности среды (pH-индуцированное высвобождение) [25]. Недавние применения данной методики позволяют проводить исследования в пикосекундном диапазоне [22,26], а также осуществлять картирование по поверхности образца в рамках методики 2D XAFS-XEOL [27,28].…”
Section: Xeol спектроскопияunclassified